Surgical Treatment of Postinfarction Thrombosed Left Ventricular Aneurysm after Bilateral Polysegmental COVID-19-Associated Pneumonia. Case Report - Gogayeva, Olena K.; Rudenko, Mykola L.; Ioffe, Natalia O. (Ukrainian Journal of Cardiovascular Surgery, 2022)
In the first year of the COVID-19 pandemic, there was a significant reduction in the number of cardiac surgeries, but recently, with the vaccination campaign, the former surgical activity is gradually recovering. Among cardiac surgery patients, many have had COVID-19. The effects of SARS-CoV-2 on the human body in general and vascular endothelium in particular cause multisystem damage, which is associated with a high risk of pulmonary, cardiac, neurological and thrombotic complications not only in the acute period but also in the long term. The issue of the timing of operations in cardiac surgery patients after COVID-19, among whom patients with complicated forms of coronary artery disease are the most severe, is very acute. Case description. Patient H., 42 y.o, was hospitalized to the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with thrombosed postinfarction aneurysm of the left ventricle, polymorbidity, severe COVID-19 with 60% lung damage 2 months ago. According to the results of diagnostic study, the on-pump surgical intervention was indicated: coronary artery bypass grafting, left ventricular aneurysm resection with thrombectomy. The predicted mortality risk was 11.5% by the EuroSCORE II scale and 8.08% by the Society of Thoracic Surgery Score (STS). The heart team decided to perform the life-saving surgery. After stabilization of the condition and compensation of concomitant diseases, the patient was successfully operated and discharged from the Institute without complications on the 9th day after surgery. Conclusions. High-risk patients with complicated coronary artery disease require careful preparation for cardiac surgery and compensation of comorbidity. Preoperative risk stratification allows the heart team to make decisions, predict perioperative complications and take measures to prevent them, as well as plan the volume of operation. Polysegmental bilateral COVID-19-associated pneumonia within the last 2 months is not a contraindication to cardiac surgery in the conditions of artificial circulation, provided adequate training, stability of the radiological picture. An important point of the positive result of cardiac surgery is intraoperative reduction of ischemic time with the performance of the main stage of the operation in conditions of parallel perfusion.